Self-medication for dysmenorrhea among Serbian medical students - Manojlović Mia S.; Tomas Ana D.; Paut-Kusturica Milica M.; Ćućuz Veljko S.; Kolarski Ivor S.; Zaklan Dragana D.; Stepanović Kristina M.; Horvat Olga J. (Hospital Pharmacology, 2021)
Introduction: Primary dysmenorrhea is a common disorder in women, with a significant impact on quality of life. Aim: The objective of this academic study was to investigate the severity of dysmenorrhea in female students of the Faculty of Medicine in Novi Sad, to estimate the self-medication prevalence of primary dysmenorrhea, to identify the most commonly used conventional, herbal, homeopathic remedies and manner of their usage, as well as non-pharmacological measures in the treatment of primary dysmenorrhea. Material and Methods: This study was performed on a random sample of 100 respondents from different departments of the Faculty of Medicine in Novi Sad, from December 1st to December 15th, 2016. The data were obtained by using a standardized questionnaire. Results: The sample included 59 female medical students and 41 female students of the other study groups. Most of the respondents had medium expressed symptoms due to dysmenorrhea (48.0%). The most common symptoms were cramps and pain in the lower abdomen, anxiety, and appetite changes. 11% of respondents were absent from classes at the university minimum one day of each menstrual cycle, because of dysmenorrhea. 66% of respondents used drugs due to symptoms of dysmenorrhea. The most commonly used group of drugs were non-steroid anti-inflammatory drugs (75.76%), primarily ibuprofen (53.03%), and diclofenac (10.61%). Self-medication prevalence was 48.48%. Conclusion: According to the results of this study, dysmenorrhea symptoms significantly impact the quality of life.